Optically pumped polaritons in perovskite light-emitting diodes - Leng, Meiying (2023)
Lead halide perovskites have achieved significant progress in light-emitting diodes (LEDs) with high efficiency in the past few decades. They are also ideal candidates for reaching the strong exciton-photon coupling regime due to their large exciton binding energy and oscillator strength. The generation and control of exotic phenomena in perovskite electroluminescent microcavities, such as electrically pumped polariton lasing and polariton LEDs, operating in the strong coupling regime at room temperature, is still a great challenge. Here, we demonstrate room-temperature strong coupling in a perovskite LED structure. The best device shows a current efficiency of 4.5 cd/A and an external quantum efficiency of 1.4% while exhibiting anticrossing behavior via optical pumping. Our approach represents a new strategy to explore ultrafast LEDs as well as electrically pumped perovskite lasing.